Relationship between Microorganisms Inhabiting Alkaline Siliceous Hot Spring Mat Communities and Overflowing Water - Becraft, Eric D. (Appl Environ Microbiol, 2020)
The compositions of Octopus Spring and Mushroom Spring (Yellowstone National Park, Wyoming, USA) microbial mats have been thoroughly studied, but the compositions of the effluent waters that flow above the mats have not. In this study, cells in the mats and overflowing waters of both springs were investigated at multiple sites where Synechococcus spp. are the dominant cyanobacteria (ca. 72°C to ca. 50°C), and on several dates. In addition to microscopic analyses of stained and autofluorescent cells, 16S rRNA gene sequencing was used to characterize the major taxa present and a protein-encoding gene (psaA) was sequenced and analyzed by ecotype simulation to predict species of Synechococcus. The mats of both springs were similar in terms of the downstream distribution of predominant taxa detected previously. However, waters above these mats were predominated by taxa that reside in upstream mats or communities above the upper-temperature limit of the mat. A disturbance/recolonization study was performed at a site normally predominated by Synechococcus species adapted to low temperatures. After removing indigenous Synechococcus cells, Synechococcus species adapted to higher temperatures, which were predominant in the water overflowing this site, colonized the newly forming mat. Differences in recolonization under reduced and UV-screened irradiance suggested that, in addition to physical transport, environmental conditions likely select for species that are better adapted to these different conditions and can influence mat recovery. A transport model was developed and used to predict that, in Mushroom Spring, erosion predominates in the narrower and deeper upstream effluents and deposition predominates over erosion in wider and shallower downstream effluents. IMPORTANCE In flowing aquatic systems, cell erosion and deposition are important to the dispersal of cells from one location to another. Very little is known about microbial dispersal and the physical processes that underlie it. This study demonstrates its importance to colonization of downstream surfaces and especially to the recolonization and functioning of disturbed sites. Ecological systems in flowing environments are often, roughly speaking, pseudosteady, in that nutrients enter the system and by-products leave at relatively steady rates. Over time, material inputs and outputs must balance. Measurements of input fluxes (e.g., growth rates and proxies, such as photosynthesis rates) are frequent. However, erosion and deposition of cells are seldom measured and ecological significance is sometimes neglected. The importance of these parameters is immediately evident in any attempt to construct a model of long-time community behavior, as spatial ecological structure is significantly impacted and can be dominated by migration of organisms, even in small numbers.